Returns to schooling, gender wage gap and discrimination in major urban labor markets in the Philippines, 2006 - Roces, Robert Dan Javier (Animo Repository, 2011)
Discrimination between social groups is often studied in many fields with the aim of measuring the impacts on certain groups and individuals. This paper contributes to the discussion further by using parametric and semiparametic models and a decomposition technique to the problem. By following the traditional method of the Mincerian Wage Functions and decomposition, the author was able to measure the male female wage differential in the local urban labor market using publicly available data. However, by using non-traditional semiparametric techniques, it was shown that the experience variable should not be discounted entirely.